Emotional Effects on Factors Associated with Chronic Low Back Pain - Ouchi K; Watanabe M; Tomiyama C; Nikaido T; Oh Z; Hirano T; Akazawa K; Mandai N (Journal of Pain Research, 2019)
Koichi Ouchi,1 Mayumi Watanabe,2–4 Chikako Tomiyama,5 Takuya Nikaido,6 Zaigen Oh,2 Toru Hirano,7 Kohei Akazawa,1 Nozomu Mandai3 1Department of Medical Informatics, Niigata University Medical and Dental Hospital, Niigata, Japan; 2Faculty of Health Sciences, Kansai University of Health Sciences, Osaka, Japan; 3Center for Humanities and Sciences, Ibaraki Prefectural University of Health Sciences, Ibaraki, Japan; 4Faculty of Science and Engineering, Chuo University, Tokyo, Japan; 5Graduate School of Health Sciences, Niigata University, Niigata, Japan; 6Department of Orthopaedic Surgery, Fukushima Medical University School of Medicine, Fukushima, Japan; 7Department of Orthopedic Surgery, Uonuma Institute of Community Medicine, Niigata University Medical and Dental Hospital, Niigata, JapanCorrespondence: Mayumi WatanabeFaculty of Health Sciences, Kansai University of Health Sciences, 2-11-1 Wakaba, Kumatoricho, Sennan-gun, Osaka 590-0482, JapanTel +81-72-453-8251Fax +81-72-453-0276Email watanabem62@gmail.comPurpose: Although chronic low back pain (CLBP) has profound effects on patients, society, and economy, its causes are difficult to identify. Psychogenic effects or social stress is known to affect CLBP; hence, investigation of its underlying causes requires a multifactorial approach. We determined the factors associated with CLBP by using an Internet-based survey. To prevent CLBP, we need to understand its cause and background.Patients and methods: A total of 1000 participants either with (+) or without (−) CLBP answered the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ), which assesses five domains of CLBP: low back pain, lumbar function, walking ability, social life function and mental health. We also administered a new questionnaire for participants, that comprised five different domains: Body, Lifestyle, Emotion, Diet, and Social. To evaluate psychogenic effects on CLBP, we added two original factors, namely outshout and HIE, which have not yet been studied. HIE is a traditional concept (sense) of “feeling cold” or “chilly.” All participants completed both questionnaires.Results: Multivariate logistic regression analysis extracted four factors (sleep, room temperature, outshout, and HIE) that were associated with CLBP. The mental health domain was assessed using the JOABPEQ for each of these factors. The factors outshout and HIE differed between CLBP (+) and CLBP (−) patients. CLBP (−) participants also showed a difference in Sleep and HIE factors.Conclusion: Among psychogenic effects, Emotion was common to all the four extracted factors. There was no common physical divisor. Therefore, we hypothesized that acute low back pain might develop into CLBP in the presence of psychological stress or other emotional factors such as outshout or HIE. Hence, we need to consider both physical and psychogenic effects in the prevention and treatment of CLBP. Furthermore, appropriate evaluation and treatment of psychological stress may be effective in reducing CLBP.Keywords: Japanese Orthopaedic Association Back Pain Evaluation Questionnaire, JOABPEQ, outshout, HIE, nonspecific low back pain